Knowledge of Sustainable Tourism and Environmental Awareness: Luang Prabang, Laos PDR - Sihabutr, Chaturaporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
Sustainable tourism takes full account of current and future economic, social and environmental impacts. Luang Prabang’s tourism progress is rooted in its natural and man-made beauty. This abundance has a positive economic impact on local businesses providing support services to the increasing number of visitors. On the other hand, the uncontrolled development from tourism activity threatens the unique atmosphere of Luang Prabang. The purpose of this study is to provide environmental tourism knowledge for tourism entrepreneurs by creating an environmental tourism booklet. Moreover, the research aims to investigate the tourism stakeholder participation in sustainable tourism and environmental tourism impacts in Luang Prabang. A semi-structured interview method was used to collect information from 44 tourism stakeholders comprising tourist entrepreneurs and local authorities, tourism boards, local communities and tourists. The research found that small establishments could implement the simple aspects of environmental awareness. Most entrepreneurs were concerned about environmental awareness because Luang Prabang is a World Heritage City under the management of UNESCO. The results also showed that some luxury hotels created a Corporate Social Responsibility Program (CSR) to enhance a sustainable environmental goal. However, the main problems relating to the environment were separating waste and reducing plastics. There was a lack of environmental campaigns from the governmental sector. The booklet distribution was useful and will raise environmental awareness among tourism entrepreneurs. The governmental sector was a significant policy-maker that can contribute to the environmental protection cycle of green enterprises by means of providing facilities, funds, knowledge transfer, and human resource management